(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: The hepatic artery is the principal arterial supply to the liver and exhibits considerable anatomical variation. Knowledge of these variations is essential for hepatobiliary surgeries, liver transplantation, radiological interventions, and laparoscopic procedures to prevent vascular injury and postoperative complications. Cadaveric evaluation of hepatic arterial anatomy provides valuable information regarding branching patterns and uncommon variants that may influence surgical planning and clinical outcomes. Aims: To study the anatomical variations in the origin, course, and branching pattern of the hepatic artery in human cadavers and to determine the frequency of common and variant hepatic arterial anatomy. Materials and Methods: This descriptive cadaveric study was conducted in the Department of Anatomy over a period of 10 months. A total of 40 adult human cadavers were included in the study. Cadavers with intact hepatobiliary and abdominal vascular anatomy were selected for dissection. Detailed abdominal dissection was performed to expose the celiac trunk, common hepatic artery, proper hepatic artery, and their branches. Variations in origin, branching pattern, accessory or replaced hepatic arteries, and arterial course were carefully identified and documented. Morphometric observations were recorded and analyzed using descriptive statistical methods. Results: Among the 40 cadavers studied, classical hepatic arterial anatomy was observed in 28 (70.0%) specimens, while variations were identified in 12 (30.0%) cadavers. The most common variation was replaced right hepatic artery arising from the superior mesenteric artery, observed in 5 (12.5%) specimens. Accessory left hepatic artery arising from the left gastric artery was identified in 3 (7.5%) cadavers. Replaced left hepatic artery originating from the left gastric artery was observed in 2 (5.0%) specimens, while accessory right hepatic artery was present in 1 (2.5%) specimen. Common hepatic artery arising directly from the abdominal aorta was identified in 1 (2.5%) cadaver. Conclusion: The hepatic artery demonstrates significant anatomical variation in origin and branching pattern. Classical anatomy was present in the majority of cadavers. Awareness of these variations is essential for surgeons, anatomists, and interventional radiologists to minimize operative complications and improve outcomes during hepatobiliary procedures and liver transplantation.